1995
DOI: 10.1007/bf00009468
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Echinostoma trivolvis (Cort, 1914) (Trematoda: Echinostomatidae) with a discussion on its identity

Abstract: The life-cycle ofEchinostoma trivolvis (Cort, 1914) has been completed experimentally and the validity and identity of this species are discussed. Synonyms for cercariae and adults of E. trivolvis are as follows: Cercaria trivolvis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 20 publications
0
70
0
Order By: Relevance
“…Additional references are denoted by superscript numbers following the common names of hosts: (3) Kanev et al (1995) , (4) Beasley et al (2005) , (5) Johnson and McKenzie (unpublished data from Colorado), (6) Ulmer (1970) , (7) McAlpine and Burt (1998) , (8) Taft et al (1993) , (9) Forrester et al (1994) , (10) Alden (1995) , (11) Sorensen et al (1997) , (12) Indicates a host species record for E. revolutum , while all other hosts listed in the echinostomatids column are records for Echinostoma trivolvis pipiens ) around this pond suffered severe limb malformations, including extra, missing, and misshapen limbs. Although some abnormalities are expected in any vertebrate population, this baseline frequency is generally low (0-5%), leading researchers to suspect that something unusual was happening at the pond.…”
Section: Vulpes Vulpesmentioning
confidence: 99%
“…Additional references are denoted by superscript numbers following the common names of hosts: (3) Kanev et al (1995) , (4) Beasley et al (2005) , (5) Johnson and McKenzie (unpublished data from Colorado), (6) Ulmer (1970) , (7) McAlpine and Burt (1998) , (8) Taft et al (1993) , (9) Forrester et al (1994) , (10) Alden (1995) , (11) Sorensen et al (1997) , (12) Indicates a host species record for E. revolutum , while all other hosts listed in the echinostomatids column are records for Echinostoma trivolvis pipiens ) around this pond suffered severe limb malformations, including extra, missing, and misshapen limbs. Although some abnormalities are expected in any vertebrate population, this baseline frequency is generally low (0-5%), leading researchers to suspect that something unusual was happening at the pond.…”
Section: Vulpes Vulpesmentioning
confidence: 99%
“…Treatment levels (10-90 cercariae) were unlikely to result in mortality and edema (Fried et al, 1997) and were within the lower end of the natural range of infections (Fried and Bradford, 1997;Skelly et al, 2006). Cercariae used for experiments were those shed from the snails in the morning corresponding to greatest shedding (Kanev et al, 1995), just prior to tadpole exposure. Cercaria shedding was induced by placing snails in small cups approximately 20 cm below a 60W incandescent light bulb (Schmidt and Fried, 1996b).…”
Section: Experimental Designmentioning
confidence: 99%
“…For the sam e reason, it is possible to explain some o f the other differences presented above. However, it is difficult to explain why Sahai & Sri vastava (1970) and w e in this paper found different num bers and different patterns o f arrangem ent o f papillae o f miracidia from Asian E. p erfo lia tu s. Based on previous studies (Kanev, 1994, Kanev et al, 1993, 1994a,b, 1995a w here adults and larvae o f different species, even o f different genera have b een found incorrectly described with a com m on name as mem bers o f a com m on species, w e suggest that perhaps the nam e E. p e r fo lia tu s was used for description o f miracidia belonging to different species. W orking in Europe, w e com pared adult worms o f E. p e r fo lia tu s from its type locality in mid-Europe with the adults from Vladivostok region, used in this study, and found no significant differences betw een them.…”
Section: For Miracidia Of E C H In O C H a S M U S Tob Imentioning
confidence: 68%